Does Raising Livestock Improve Household Food Security and Child Dietary Diversity in a Rural Region of Madagascar? - Fanantenana Raholiarimanana; Hasina Rakotomanana; Akira Ishida (MDPI AG, 2023)
Madagascar is one of the poorest countries and has an alarming prevalence of food insecurity and child undernutrition. Most of the Malagasy population live from agricultural activities making livestock a livelihood asset and a source of animal-source foods, especially for smallholder farmers. This study aimed to examine the association between livestock ownership, household food security, and children's dietary diversity in a rural region of Madagascar. Data from a cross-sectional survey of 344 respondents were used to assess the association between household tropical livestock units (TLU) per capita, Household Food Insecurity Access Scale (HFIAS) scores, and dietary diversity scores (DDSs) among children aged 6-23 months. The estimation results from the ordered probit model showed that household TLU per capita is negatively associated with HFIAS scores and positively associated with DDSs among children. Additionally, households with mothers who received information on childcare and nutrition from health facilities and community nutrition agents were more likely to be food secure and have better dietary diversity. Therefore, promoting livestock ownership and strengthening nutrition-sensitive messages focusing on the benefits of raising livestock to mothers from rural Madagascar will likely be effective in improving household food security and nutrition for children.